Health-related quality of life and associated factors in heart failure with reduced ejection fraction patients at University of Gondar Hospital, Ethiopia - Belay Agonafir, Daniel; Mulat Worku, Biruk; Alemu, Hailemaryam; Nega Godana, Tilahun; Fentahun Bekele, Shibabaw; Andargie Berhane, Abel; Getahun Ayalew, Desalew; Sisay Assefa, Belete; Alemiye Molla, Fikadu; Lema Legese, Gebrehiwot (Frontiers in Cardiovascular Medicine, 2024)
Introduction Living with heart failure poses challenges due to its poor prognosis and impact on quality of life, making it crucial to assess how it affects patients for better patient-centered management. This study aimed to assess quality of life and associated factors in heart failure with reduced ejection fraction patients at University of Gondar Comprehensive Specialized Hospital in Ethiopia, 2023. Methods An “institution-based” cross-sectional study was conducted at the University of Gondar Comprehensive Specialised Hospital. The data were collected using an interviewer-administered questionnaire. Health-related quality of life was measured using the Minnesota Living with Heart Failure Questionnaire. Sociodemographic, behavioral, clinical, biochemical, and echocardiographic characteristics were included in the questionnaire. The collected data were entered into EpiData version 4.6 and exported into SPSS version 25 for analysis. Multiple linear regression analysis (p < 0.05) was used to measure the degree of association between quality of life and independent variables. Results A total of 240 patients with heart failure and reduced ejection fraction participated in the study. The health-related quality of life scores for the physical, emotional, and total were 17.60 ± 10.33, 10.58 ± 6.33 and 46.12 ± 26.06, respectively. Health-related quality of life was significantly associated with age, marital status, occupation, income, heart failure duration, recent hospitalization, New York Heart Association functional class, heart failure etiology, atrial fibrillation comorbidity, systolic blood pressure, heart rate, heart failure medications, severe left ventricular systolic dysfunction, and severe or moderate pulmonary hypertension. Conclusion This study found that patients with heart failure and reduced ejection fraction had poor health-related quality of life, influenced by identified factors. These findings aid professionals in assessing and identifying interventions that improve these patients’ quality of life.